The Commodification of Security in Brazil: Urban–Rural Divide in Household Adoption of Safety Protective Devices. Issue 2 (3rd April 2022) - Aransiola, Temidayo James; Ceccato, Vania; Justus, Marcelo
Abstract : This study aims to assess the determinants of using safety devices in Brazilian households, taking into account different urban–rural country contexts and income distribution. Probit models are estimated using microdata from the 2009 Brazilian National Household Sampling Survey. On average, less than half of the underprivileged population adopts safety devices, whereas almost double as many do so among the wealthy. Findings also indicate an inverse association between the level of urbanization and adoption of safety protective devices, especially of modern ones—a pattern mediated by individual levels of victimization and safety perceptions. For example, previous victimization by theft or robbery is more decisive for adopting safety protective devices among economically underprivileged households compared to wealthier ones. These results provide evidence of the perverse effects of unequal commodification of security across a country that penalizes, in particular, the rural poor.